2009
DOI: 10.1063/1.3058602
|View full text |Cite
|
Sign up to set email alerts
|

A design for a subminiature, low energy scanning electron microscope with atomic resolution

Abstract: We describe a type of scanning electron microscope that works by directly imaging the electron field-emission sites on a nanotip. Electrons are extracted from the nanotip through a nanoscale aperture, accelerated in a high electric field, and focused to a spot using a microscale Einzel lens. If the whole microscope ͑accelerating section and lens͒ and the focal length are both restricted in size to below 10 m, then computer simulations show that the effects of aberration are extremely small and it is possible t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2010
2010

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…The simulated properties of our 500 nm electrostatic lens system were reported in a previous paper [11], where the first electrode is used to accelerate the electrons, and the rest are used to create an Einzel lens (figure 1). In these simulations, it was shown that a focused beam spot size of 1.24 nm is possible to achieve at a working distance of 4.9 μm with a unit beam magnification, while the dominant chromatic aberrations were estimated to be as low as 0.02 nm.…”
Section: Designmentioning
confidence: 99%
See 1 more Smart Citation
“…The simulated properties of our 500 nm electrostatic lens system were reported in a previous paper [11], where the first electrode is used to accelerate the electrons, and the rest are used to create an Einzel lens (figure 1). In these simulations, it was shown that a focused beam spot size of 1.24 nm is possible to achieve at a working distance of 4.9 μm with a unit beam magnification, while the dominant chromatic aberrations were estimated to be as low as 0.02 nm.…”
Section: Designmentioning
confidence: 99%
“…This makes it possible to obtain a bright electron beam with a high resolution at low voltages, where even the dominant chromatic aberrations can be significantly reduced [8,9]. Based on this idea of down-scaling, extensive work has been done to develop practical low-energy electron-beam systems as early as 1976 [10], and progress in nanofabrication and metrology has generated a renewed interest in such devices [7,9,[11][12][13][14][15][16][17]. Consequently, complex electron-beam systems with column dimensions in the millimeter range have been developed [14,15].…”
Section: Introductionmentioning
confidence: 99%